APPLICATION OF ARTIFICIAL INTELLIGENCE IN ACCOUNTING AND FINANCE: REVIEW AND BIBLIOMETRIC ANALYSIS - Ghassani, Ajrina; Sari, Diana; Marselian, Samuel (Jurnal Ilmiah Ekonomi Bisnis, 2024)
Artificial Intelligence (AI) applications in Accounting and Finance garnered attention and a significant research interest. Although recent years have shown a descent in publication volume. The type of research is qualitative data using bibliometric analysis of the application of Artificial Intelligence (AI) in Accounting and Finance from 2021 to 2024, using data from scholarly articles the study employs bibliometric methods including citation analysis, publication trends, and network visualization using VOSviewer and Publish or Perish (PoP) Software. This analysis identifies the top 10 publishers in Artificial Intelligence (AI) in Accounting and Finance. Elsevier with 244 articles, and Springer with 117 articles. MDPI with 65 articles, Emerald with 64 articles. Wiley Online Library with 53 articles, Taylor & Francis with 52 articles, Sage Publications with 24 articles, and IEEE with 21 articles. CEEOL and ResearchGate with 19 articles each. These publishers have made significant contributions to advancing AI research in this field in recent years. Future research should analyze factors influencing the publication descent and explore innovative AI solutions to financial inclusion challenges.